Interactive effects of LED lightings and nitrogen on growth and physiological processes of lettuce (Lactuca sativa l.) - Anuar, Norfadhillah (2018)
Inefficiency of traditional growing lights led the use light-emitting diode (LED), which is characterized as energy efficient, long operating lifetime, low maintenance cost and do not emit excessive radiant heat. Plants growth under varying irradiance regimes have different physiological behaviour thus it respond differently to different levels of nutrient availability. The study reported here was aimed at evaluating the impact of various regimes of LED lights on lettuce (Lactuca sativa) grown under different rates and sources of nitrogen. To evaluate the interaction effects between LED lightings and rate of nitrogen on growth and physiological processes of two varieties of lettuce, an experiment involving five light regimes [L1-red/blue (126 μmol m-²s-1), L2-red/blue (170 μmol m-²s-1), L3-red/blue/far-red/white (266 μmol m-²s-1), L4-red/blue/fluorescent (201 μmol m-²s-1) and L5-red/blue/far-red (183 μmol m-²s-1)], three additional nitrogen rate (0, 7.5 and 15 g urea L-1) and two lettuce variety (Iceberg and Butterhead) were conducted. Plants grown under L3 with combination spectrums of red, blue, far-red and white with the highest intensity (266 μmol m-²s-1) produced the highest yield. Plants under L4 and L3 had higher net photosynthesis compared to those grown under L1, L2, and L5. Leaf of lettuce under L3 contained the lowest nitrogen and potassium percentage. Increasing N rate from 7.5 and 15 g urea L-1 did not markedly affect the growth and chlorophyll content of leaves, despite the increase in leaf nitrogen, calcium and magnesium contents in leaves. The interactive effects of five light regimes (as in earlier experiment), three nitrogen sources (Urea, KNO3 and Ca(NO3)2) and two rates (3.45 and 6.9 g N L-1) of nitrogen on butterhead lettuce were examined in the following experiment. Lettuce grown under L3 was the most superior in yield compared to those grown with other lights regimes. The yield of lettuce grown under L3 was 98.03 g plant-1, whereas the lowest yield was belonged to plants grown under L1 (57.51 g plant-1). Plant height, number of leaves and total leaf area were positively correlated to the yield. Nitrate content in leaves was significantly affected by the light regimes with plants grown under L3 and L4 contained the lowest concentration of nitrate. Amongst nitrogen sources tested, use of urea had resulted in heaviest yield with the lowest nitrate content in leaves. Application of urea and KNO3 had significantly influenced the content of total phenolic and total flavonoid in lettuce. N rate of 6.90 g N L-1 generated significantly higher leaf number, yield, total leaf area, leaf nitrogen, nitrate and total phenolic contents in butterhead lettuce compared to those grown under 3.45 g N L-1 . In conclusion, growth and physiological processes of lettuce were found to be significantly affected by the light regimes, nitrogen rate and sources of nitrogen. Within limitation of the current study, it was found that LED light with red, blue, far red and white LEDs (L3, 266 μmol m-2s-1) coupled with urea given at 7.5 g N L-1 had produced the highest yield and lowest nitrate content in lettuce.